One Size Does Not Fit All: Ethical Oversight Across Human Factors Domains and Practices. (September 2022) - Dickerson, Kelly; Straut, Theresa; Vaughan, Barry; Rauschenberger, Robert; Flint, Jesse; Buda Smith, Natalie; Giari, Katie
In regulated institutions "research" has a narrow and specific meaning, which often excludes many types of information gathering engagements common in applied environments. Additionally, researchers in applied fields such as user and customer experience, where formal degree programs are not a typical training path, foundational ethical documents like the Belmont report may have never been studied. The ethical landscape gets even more complex when considering product and safety-related research. Investigators want to act ethically, but the needed steps to do so are not always clear and ethics and organizational needs are not always well aligned. The result is a diverse ecosystem of local policies, best practice guides, "playbooks" and folk knowledge. This panel gathers a diverse group of investigators and regulators from government and industry to discuss the challenges of working in regulated and non-regulated environments while comparing strategies, techniques, and engaging in an open dialogue with the HFES community.